Global research progress of visceral hypersensitivity and irritable bowel syndrome: bibliometrics and visualized analysis - Tian, Siyu; Zhang, Hang; Chen, Siqi; Wu, Pengning; Chen, Min (Frontiers in Pharmacology, 2023)
Background: Irritable bowel syndrome (IBS) is a group of functional intestinal disorders characterized by abdominal pain, bloating, and changes in bowel habits, and/or stool characteristics. Recent studies have shown that there has been a significant advancement in the study of visceral hypersensitivity in IBS. Through the use of bibliometrics, this study aims to provide a comprehensive overview of the knowledge structure and research hotpots of visceral hypersensitivity in IBS. Methods: Publications related to visceral hypersensitivity in IBS from 2012 to 2022 were searched on the web of science core collection (WoSCC) database. CiteSpace.6.1. R2 and Vosviewer 1.6.17 were used to perform bibliometric analysis. Results: A total of 974 articles led by China and the United States from 52 countries were included. Over the past decade, the number of articles on visceral hypersensitivity and IBS has steadily increased year by year. China, the United States, and Belgium are the main countries in this field. Univ Oklahoma, Univ Gothenburg, and Zhejiang University are the main research institutions. Simren, Magnus, Greenwood-van meerveld, Beverley, and Tack, Jan are the most published authors in this research field. The research on the causes, genes, and pathways involved in visceral hypersensitivity in IBS and the mechanism of IBS are the main topics and hotspots in this field. This study also found that gut microbiota may be related to the occurrence of visceral hypersensitivity, and probiotics may be a new method for the treatment of visceral hypersensitivity and pain, which may become a new direction for research in this field. Conclusion: This is the first bibliometric study to comprehensively summarize the research trends and developments of visceral hypersensitivity in IBS. This information provides the research frontier and hot topics in this field in recent years, which will provide a reference for scholars studying this field.